2019
DOI: 10.5944/ap.16.1.22180
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la regulación emocional: indicadores psicométricos del instrumento RPA en población española

Abstract: En la investigación clínica, el afecto positivo ha recibido menos atención que su dimensión paralela: el afecto negativo. Este trabajo analiza las propiedades psicométricas de la Escala de Afectividad Positiva (Response to Positive Affect), para su adaptación al castellano y validación en población española. La escala mide las respuestas a las emociones experimentadas ante situaciones positivas (regulación emocional). Según los autores de la escala, está compuesta por tres factores: Amortiguación, Rumia positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…In this study we isolated two factors in the RPA compared to the three factors extracted in the studies reviewed (Feldman et al, 2008;Hidalgo-García et al, 2019;Krais et al, 2019;Olofsson et al, 2014;Raes et al, 2009;Yang & Guo 2014). This is consistent with other studies (Abasi et al, 2018;Voss et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In this study we isolated two factors in the RPA compared to the three factors extracted in the studies reviewed (Feldman et al, 2008;Hidalgo-García et al, 2019;Krais et al, 2019;Olofsson et al, 2014;Raes et al, 2009;Yang & Guo 2014). This is consistent with other studies (Abasi et al, 2018;Voss et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…Results showed that the two-factor structure had better fit in all the analyses, with adequate indices (Hu & Bentler, 1999;Kline, 2015). Measurement invariance tests showed total configural, metric, scalar and strict invariance across gender (Hidalgo-García et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations